Photo-crosslinking and layer-by-layer processed organic photodetectors with remarkably suppressed dark current - Hun Jee, Min; Park, Byoungwook; Young Lee, Ah; Rhee, Seunghyun; Lim, Minyoung; Min Ha, Jung; Kim, Nayoung; Zhang, Fujun; Ha, Jong‐Woon W.; Ahn, Hyungju; Kim, Jong H.; Han, Mijeong; et al. (Chemical Engineering Journal, 2024)
The effective reduction of dark (or noise) current presents a significant hurdle in enhancing the detectivity of organic photodetectors (OPDs). To address this challenge, a photo-crosslinkable donor polymer, PM6-Br50, is synthesized by introducing bromoalkyl side-chains onto the PM6 structure. This modification enables the formation of a pseudo planar heterojunction (p-PHJ) structure of crosslinked donor/acceptor through a layer-by-layer (LbL) sequential process without the necessity for an semi-orthogonal solvent. This innovation effectively overcomes solvent-related limitations in the LbL process. Additionally, we replace the semi-metallic hole-transport layer (HTL), PEDOT:PSS, with a semiconducting conjugated polyelectrolyte (TPAFS-TMA) with a high conduction band. The p-PHJ configuration, featuring pure donor/anode and pure acceptor/cathode contacts, enhances the charge injection barrier for electrons (holes) from the anode (cathode) in the dark under reverse bias, effectively minimizing dark current. Furthermore, the TPAFS-TMA HTL serves to impede electron injection from the anode. Through the synergistic combination of these two strategies, a significantly reduced dark current density (4.03 × 10−10 A cm−2) is measured by four orders of magnitude, compared to the bulk heterojunction OPDs with PEDOT:PSS. Furthermore, we measure remarkably high shot noise-based and total noise current-based specific detectivities of 4.27 × 1013 and 6.97 × 1012 cm Hz1/2 W−1 (with linear dynamic range of 73.7 dB), respectively.
Keywords: Conjugated polyelectrolytes; Crosslinkable polymers; Hole transport layers; Layer by layer; Noise current; Organic photodetector; Organics; PEDOT/PSS; Photo-crosslinkable polymer; Pseudo planar heterojunction; Conjugated polyelectrolyte; Dark current; Organic photodetector; Photo-crosslinkable polymer; Pseudo Planar heterojunction